56.6k views
0 votes
Simplify -x-(-4x-6)=6

User Stanni
by
4.8k points

1 Answer

2 votes

Answer:

To simplify the given equation, we can start by using the rules of algebra to rearrange the terms and combine like terms on both sides of the equation. This gives us:

-x - (-4x - 6) = 6

We can then distribute the negative sign on the left side of the equation to get:

-x + 4x + 6 = 6

We can then combine like terms on the left side of the equation to get:

3x + 6 = 6

We can then subtract 6 from both sides of the equation to get:

3x = 0

We can then divide both sides of the equation by 3 to get the final result:

x = 0

Therefore, the simplified form of the given equation is x = 0.

Explanation:

User Stefan Fisk
by
5.4k points